Impact of Multi-Disciplinary Care and Clinical Coach Coordinators on Participant Satisfaction and Retention in TBI Clinical Trials: A TEAM-TBI Study. (21st March 2019) - Mesley, Matthew S; Edelman, Kathryn; Sharpless, Jane; Borrasso, Allison; Billigen, Julia B; Puffer, Ross; Williams, Dana; Benso, Steven; Puccio, Ava M; Schneider, Walt; Soose, Ryan; Beers, Sue; et al.
Abstract: Background: Targeted Evaluation Action and Monitoring of Traumatic Brain Injury (TEAM-TBI) is a monitored, multiple interventional research identifying clinical profiles and assigns individualized, evidence-based treatment program. The objective of the current study was to assess overall participant satisfaction of the multi-disciplinary care team and approach. Methods: Between 2014 and 2017, 90 participants completed the 4-day TEAM-TBI clinical intake evaluation resulting in individualized treatment recommendations followed by a six-month intervention phase follow-up. Inclusion criteria were: age 18–60, history of chronic TBI (>6 months post-injury) with refractory clinical sequelae at screening (Post-Concussion Symptom Scale [PCSS] score >30). Results: A total of 85/90 (94%) participants completed the survey at baseline focusing on intake evaluation and approach; 90% of eligible participants also completed the follow-up time-point. Hundred percent of participants had a mean score of >4 across all questions at the initial time point." Conclusions: The multi-disciplinary care approach and individualized treatment plans of the TEAM-TBI study yielded high participant retention and satisfaction scores. The Clinical Coach component of the trial was one of the highest rated aspects of the program and was associated with participant motivation and high retention rates.